Eighth Five Year Plan 1992-97 Volume I : Objectives, Perspective, Macro-Dimensions, Policy Framework and Resources - Planning Commission, Government of India (Planning Commission, Government of India, 1992)
We now have a robust and resilient agricultural economy with near self-sufficiency in food production. We have built a diversified industrial and service structure. We have a large pool of skilled manpower and ample entrepreneurial capabilities. The growth performance of at least a decade proceeding the Eighth Plan has been impressive. We have the wherewithal for further progress. Hence, the task before the Eighth Plan is to use these advantages for further growth and lay strong foundations for even higher growth in the future.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Eighth Five Year Plan- India